Development and characterization of readout electronics for neutron scattering instrumentation - Lojius, Lombigit (2012)
In the field of material characterization, the neutron scattering technique is found to be useful in many applications. This technique requires a position sensitive neutron detector (PSND) and their readout electronics to detect the position of neutron interactions. Fast, high count rate and high positional resolution PSND such as the 3He-filled Multi-Wire Proportional Counter (MWPC) is designed for specific applications and has unique technical specifications. Therefore, it requires customised readout electronics which capable of accepting a wide range input signal, good noise/ENC performance or fast signal processing to match their specifications. In order to optimize the detector’ performance in terms of speed, count-rate, and positional resolution, the individual readout method is often employed as positional encoding method to detect the neutron interactions. In this method, each wire are connected to an individual readout electronic and if the applications requires large active area detector, a large number of readout electronics are required thus, increased the development cost. This study presents the design and development of readout electronics comprise of an eight (8) channels low noise charge sensitive preamplifier-pulse shaping amplifier (CSP-PSA) chain capable of accepting a wide range input signal and fast signal processing which is ideal for high count rate and high position resolution neutron scattering instrumentations. The readout electronic circuit is built entirely with low-noise FET-input operational amplifier (Op-amp) and passive components. The time constant for charge sensitive preamplifier (CSP) is around 250 ns and it is equipped with an additional T-network at output stage. The pulse-shaping amplifier (PSA) is designed based on a fifth-order complex-pole semi-Gaussian filter;comprising a cascade first-order high-pass filter (HPF) with pole-zero (PZ) cancellation networks and two second-order Sallen-Key low-pass filters (SK LPF). These circuits are designed using Laplace transform then verified with macro model component-based simulation. A series of testing had been carried out to measure how well the actual performance fulfilled the major objective. These procedures include measurements of direct-current (DC) offset, dynamic range, gain, linearity, electronic noise and analysis of time over threshold (TOT). The development cost of the readout electronics is around U.S $50/channel,which is suitable for low-cost applications. Results showed that the readout electronics has good electronic noise with measured Equivalent Noise Charge (ENC) average at 2108 e- ± 10% and insensitive to input capacitance variation (25 e-/pF). Charge calibration using the TOT method shows that it can separate small difference of charge and capable of accepting a wide dynamic range input charge (20-600 fC) with excellent linearity (nonlinearity < 1%). Fast peaking time around 300 ns and short pulse width around 1.2 - 1.6 us, shows that it can be used for fast detector with count rate capability below 50 kHz at 10% dead time.